Chatgpt dan Konstruksi Otoritas Keagamaan Generasi Z: Implikasinya Terhadap Pembelajaran Pendidikan Agama Islam - Anjas Ardana; Kurnia Kristiyaningrum; Rizka Harfiani (UIN Sumatera Utara, 2026)
The emergence of Artificial Intelligence (AI) based on Large Language Models has drastically altered how Generation Z acquires and develops religious knowledge. One of the most popular generative AI apps, ChatGPT, is being used more and more to quickly and interactively get Islamic information. The use of ChatGPT as a source of religious information, the development of Generation Z's trust in ChatGPT, the reconstruction of religious authority that results from its use, and its consequences for Islamic Religious Education (IRE) learning are all examined in this study. This study used a phenomenological design and a qualitative methodology. Semi-structured interviews, observations, and documentation of Islamic Religious Education students who had utilized ChatGPT to look for religious information were employed to gather data. Braun as well as Clarke's Reflexive Thematic Analysis was used to analyze the data. The findings highlight four important themes. First, students can obtain a basic awareness of a variety of Islamic concerns by using ChatGPT as a useful, quick, and accessible source of religious information. Second, rather than being based on ChatGPT's religious authority, students' belief in it is mostly instrumental in nature, based on its value for information retrieval. Third, a reconstruction of religious authority is occurring in the form of hybrid religious authority, which is defined by the interplay between the mediating function of digital algorithms in knowledge acquisition and the conventional academic authority of religious scholars and educators. Fourth, the expansion of ChatGPT promotes a change in Islamic Religious Education that necessitates the development of digital literacy, religious AI literacy, and religious literacy. This study comes to the conclusion that AI changes how Generation Z receives, validates, and creates religious information in the digital age rather than displacing conventional religious authority.